Antioxidative Activity of Andaliman Fruit Extract (Z. acanthopodium DC.) on Several Food System and its Antioxidative Stability on Temperature and pH Influence - Tensiska .; C Hanny Wijaya; Nuri Andarwulan (Jurnal Teknologi dan Industri Pangan, 2003)
The extraction of the andaliman fruit was conducted by using ethanol, and hexane. The hexane residue was reextracted by ethanol. The protection factor of the extracts is 3.823, 1.486, and 3.84 respectively. While the protection factor of BHT is 2.828. The research shows that andaliman fruit extract has the highest antioxidative activity on aqueous system. While in emulsion and oily system, andaliman extract still have a moderate activity. The antioxidative activity is relatively stabile during heating. Heating up to 175Ã¢â‚¬Å¾aC in aqueous system for 2 hours is merely reduce the activity to 17%. The protection effect increase during the increasing of pH (examined at pH 3,4,5,6, and 7), except at pH 4. Key words : Andaliman, antioxidative activity, heating, and pH.